Don't let them smash the NGA, 1985 (London, 1985)
1985 1980-95 "Don't let them smash the NGA, 1985" [BW0030], 1985, Trades Union Congress The Newspaper Society launched its 'Project Breakthrough' to introduce new technology in 1982. The National Graphical Association was concerned that the closed shop for typesetting would be ended and wages and conditions in the industry would worsen. In 1985, the NGA had disputes at the Wolverhampton Express and Star, the Shropshire Star and the Kent Messenger over new technology and working practices.